Growth, Structural, Second Harmonic Generation and Quantum Chemical Analysis of N,N’-Diphenylguanidinium Nicotinate Hydrate - G, Saravana Kumar (Orbital: The Electronic Journal of Chemistry, 2023)
Solution growth approach was used to create N,N՛-Diphenylguanidinium Nicotinate Monohydrate (DPGNH) single crystals with a fine habitat. X-ray diffraction examination of a single crystal revealed the structural characteristics. Density Functional Theory (DFT) investigations were carried out to divulge the structural, spectral, Frontier Molecular Orbitals (FMO’s) and Non-Linear Optical (NLO) properties of N,N՛-Diphenylguanidinium Nicotinate Monohydrate (DPGNH) at molecular level. The molecular structure of DPGNH was optimized utilizing B3LYP/6-31G (d,p) level of theory. This optimized molecular structure was further used to examine the computed UV-vis spectra. The FMO’s were further explored to known about the electron transfer within DPGNH molecule. In order to shed light on the Second Harmonic Generation (SHG) at the molecular level, the NLO characteristics were evaluated using DFT. By using the Kurtz-Perry powder approach, the experimental Second Harmonic Generation (SHG) was examined.